Pengaruh Phet Terhadap Berpikir Kritis Materi Matematika Kelas IV SDN Banyuajuh 3 - Hana, Adela; Indra Perdana, Parrisca (ALENA : Journal of Elementary Education, 2024)
This research aims to find out the influence of PhET simulation on students' critical thinking in class IV Mathematics at SDN Banyuajuh 3. This research uses experimental quantitative methods with a comparative research type, and uses a Quasi Experimental Design in the form of Nonequivalent Control Group Design. The subjects of this research were 56 students in grades 3 and 4 of SDN Banuaajuh. This research data was collected through questionnaires, observation sheets and tests. The hypothesis test used in this research is the comparative t test of two independent samples. The results of the test data analysis with a significance level of 0.05, if the calculated value > ttapata (7.727 > 2.004) then H0 is rejected, Ha is accepted, students have different scores. Critical thinking test between experimental and control groups. These results are supported by the finding that the level of critical thinking observed among students in the experimental group was 82% > 70% of the level of critical thinking in the control group. Therefore, it can be concluded that the use of PhET descriptive analysis influences students' critical thinking in class IV Mathematics at SDN Banyuajuh 3.